Possibilities for the correction of functional disorders of the biliary tract and parasitic infestations in young children using the plant complex Vormil Phyto - K.V. Savytska (Zdorovʹe Rebenka, 2017)
Recently, there has been a significant growth in parasitic invasions among young children. At a younger age, parasitic infestations most often occur “under the mask” of gastroenterological pathology. At this age range, according to the domestic and world literature, functional diseases prevail. In May 2016, at the week of American gastroenterology, the Rome criteria IV were adopted. According to the the Rome criteria IV, as well as in the previous editions, it is suggested to prescribe therapy on the basis of the predominant symptom principle, giving preference to so-called complementary and alternative medicine, and, in particular, phytotherapy as additional therapy for the disease, but all also from the standpoint of evidence. The first such combined phytocomplex, which attracted interest from clinical researchers and patients, is Vormil Phyto — a mix of extracts of thirteen plants. The purpose of our research was the improvement of therapeutic approaches to the correction of the combined functional pathology of the biliary tract and parasitic invasion, as well as unassociated pathology of the biliary tract using phytocomplex Vormil Phyto in the main treatment regimens. Sixty children were divided into three groups: the first group with combined functional disorder of the biliary tract and parasitic infestation; the second group with a functional biliary tract disorder, received the phytocomplex Vormil Phyto; the third group with a functional biliary tract disorder, received traditional therapy. In the course of the research, data were obtained that indicate the effectiveness of the phytocomplex Vormil Phyto, which has not only an antihelmintic effect, but also normalizes the kinetics of the biliary tract that improves appetite rapidly and does not induce dyspeptic symptoms at earlier terms.